2008
DOI: 10.4141/cjss07086
|View full text |Cite
|
Sign up to set email alerts
|

Soil and crop responses to long-term potato production at a benchmark site in northwestern New Brunswick

Abstract: Concerns about deteriorating soil quality led to Agriculture and Agri-Food Canada establishing a network of 23 soil quality monitoring benchmark sites with the objective of providing a baseline data set for assessing change in soil quality and biological productivity of representative Canadian farming systems. A site (22-NB) was established in 1990 in northwestern New Brunswick to monitor changes in Podzolic and Brunisolic soils developed on coarse loamy till on a rolling landscape under intensive potato (Sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…resulting from site position (e.g., flat, steep slope, riverine, etc.) (Rees et al 2008). Inclusion of farm dummy variables also acted as a control for omitted variables and accounted for unobserved time-invariant characteristics that might be correlated with the dependent variable.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…resulting from site position (e.g., flat, steep slope, riverine, etc.) (Rees et al 2008). Inclusion of farm dummy variables also acted as a control for omitted variables and accounted for unobserved time-invariant characteristics that might be correlated with the dependent variable.…”
Section: Methodsmentioning
confidence: 99%
“…In another New Brunswick study, Chow et al (1999) found that terraces and grassed waterways reduced runoff and soil loss, thereby increasing available water for plant growth. Rees et al (2008) found that upper terrace cross sections within a field consistently had higher potato yields compared to the lowest terrace. They reasoned that potato yields may have been affected by microclimate and other site position soil differences.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…They are the least common of the Brunisols, with total aerial extent of 21 500 km 2 . (Wang et al 1984;Rees et al 2008). An example of a cultivated Orthic Sombric Brunisol from the Fraser River Delta in British Columbia is given in Fig.…”
Section: Sombric Brunisol Great Groupmentioning
confidence: 97%
“…Long-term mineral fertilizer additions to the Fredericton loam sustained timothy hay production in the Saint John River valley (Rees and Fahmy 1984) and years of manure application to the Pitt's Pond soil in central Newfoundland have significantly increased forage production (Hender 1986).…”
Section: Agricultural Management On Brunisolic Soilsmentioning
confidence: 99%